(untitled) (American Journal of Islam and Society, 2006)
With the noble aims of conflict resolution and peace building, Lawrence G. Potter and Gary G. Sick have compiled an excellent collection of essays on “the war without winners” (p. 2). This remarkable publication, Iran, Iraq, and the Legacies of War, adds to Potter and Sick’s series of co-edited books on Middle Eastern issues, namely, The Persian Gulf at the Millennium: Essays in Politics, Economy, Security, and Religion (Palgrave Macmillan: 1997) and Security in the Persian Gulf: Origins, Obstacles, and the Search for Consensus (Palgrave Macmillan: 2002). Potter and Sick are two prominent scholars of international affairs at Columbia University. During the Carter presidency, Sick served as the principal White House aide for Iran on the National Security Council. (Sick is well-known for his exposé All Fall Down: America’s Tragic Encounter with Iran [Random House: 1985]). This 224-page book was written in the cautiously hopeful belief that the time has come for reconciliation to begin. It contains nine chapters plus Potter and Sick’s helpful introduction, which contextualizes the futile war that shook the world. The Iran-Iraq war was one of the longest and costliest conventional wars of the twentieth century. Although the number of casualties is still in dispute, an estimated 400,000 were killed and perhaps 700,000 were wounded on both sides (p. 2). The Economist commented that “this was a war that should never have been fought … neither side gained a thing, except the saving of its own regime. And neither regime was worth the sacrifice” (p. 2) ...